Analysis of Sustainable Arjuno Agro Techno Park (AATP) Development in Pasuruan Regency - Brehaspati, Eka Wara; Riniwati, Harsuko; Ciptadi, Gathot; Putra, Fadillah (Journal of Indonesian Tourism and Development Studies, 2023)
Tourism is one of the most strategic development sectors, with a direct or indirect multiplier effect that benefits a country's social, cultural, educational and economic sectors. The tourism sector plays an important role in improving the national economy, especially reducing unemployment and increasing state productivity. Pasuruan Regency has UPTD Cultivation of Cattle Sumberejo which receives funding from the government, but always loses money so the government redesigns the UPTD Cattle Cultivation area into Arjuno Agro Techno Park (AATP) as an eco and edutourism area, education and training, research center, and livestock cultivation. The Arjuno Agro Techno Park (AATP) area is supported by the existence of a number of natural tourist destinations, as well as coffee and durian plantations. The purpose of this study is to analyze opportunities for improving the sustainable development of Arjuno Agro Techno Park in Pasuruan Regency in an effort to support the revival of the tourism sector. The type of research used is a type of quantitative research with a descriptive approach. Data collection techniques using questionnaires, interviews and focus group discusion. The samples used are experts who have a lot of information and great strength for the sustainable development of Arjuno Agro Techno Park. The results indicate that six scenarios, namely formal education, training, livestock production, ICT, ecotourism and infrastructure, have great opportunities to support the realization of sustainable Arjuno Agro Techno Park (AATP) development in Pasuruan Regency.